KINERJA APARATUR BIDANG KOPERASI USAHA MIKRO KECIL MENENGAH DINAS PERINDUSTRIAN PERDAGANGAN KOPERASI UMKM PERTAMBANGAN DAN ENERGI KABUPATEN PONTIANAK - Eka Sari Rahmadani E.42009013 (FISIP Universitas Tanjungpura Pontianak, 2022)
The thesis entitled ‘’Performance of Government Official Cooperative SME Mining Industry Trade and Energy Cooperation Pontianak regency’’. Thesis writing is intended to to be considered for the leadership to make improvements to employee performance in the Department of Industry, Trade and Energy Cooperation SME Mining District Cooperative Division Pontianak especially on SMEs. The title of this thesis was appointed by barkaitan employee performance problems with the quality, quantity and timeliness of completion of work by employees in Cooperative Sector SMEs. This research uses descriptive qualitative research approach. Domain analysis (Domain Analysis) which describe, explain and describe the process of performance on SMEs Cooperatives Cooperatives Department of Trade of Industry Mines and Energy SMEs Pontianak regency. The research subject is particularly Pontianak District Government Department of Industry, Trade and Energy Cooperation SME Mining Pontianak regency. The conclusion of this study is the lack of kuntitas employees, lack of employee understanding of the technology, lack of infrastructure and funds to support the implementation of activities. The recommendation for a given policy is the addition quantity of employees, the training on computer technology, especially for the employees, and improve facilities and infrastructure to support the implementation of activities. Keyword: Quantity employees, knowledge of technology, facilities and infrastructure.